Characterization and Effectiveness Testing of a Transdermal Patch Combining Red Betel Leaf Extract and Tapak Liman Extract for the Healing of Diabetic Gangrene Wounds - Hanun Aishy Marwa; Nadine Ayu Syaima Gustaf Prins; Alliva Ro’ain Abbiyu Imanita; Fania Putri Wiba Maharani; Rahmawati Salsa Dinurrosifa (Postgraduate, University of Mataram, 2025)
This study aimed to develop and evaluate three nanogel-based transdermal patch formulations combining red betel leaf (Piper crocatum) and tapak liman (Elephantopus scaber L.) extracts to accelerate diabetic gangrene wound healing. The extracts were obtained by maceration using 70% ethanol and qualitatively indicated flavonoid-like compounds through color reactions and TLC profiles. The nanogel was prepared from a nanoemulsion containing Tween 80, PEG 400, olive oil, and distilled water, then incorporated into a carbopol-based gel matrix with propylene glycol, triethanolamine, and nipagin. The mixture was dried in an oven at 50 °C and stored in a desiccator for 24 hours to form a stable patch. Physical evaluation showed a pH of 6.0–6.7, patch thickness of 0.106–0.113 mm, and nanoparticle sizes of 74.46, 108.2, and 118.7 nm for Formulas 1–3, respectively. In vivo testing used diabetic rats divided into five groups: positive control (iodine plaster), negative control (untreated), and Formulas 1–3 with extract ratios of 3:1, 1:1, and 1:3. Formula 3, with a particle size of 118.7 nm, achieved complete wound closure by day 7. These findings highlight the potential of this nanogel-based transdermal system as a promising foundation for developing effective topical therapies for diabetic gangrene wounds